Integrated modeling for simulating sediment production and transport in agricultural landscapes. (February 2023) - Lee, Sanghyun; Chu, Maria L.; Guzman, Jorge A.; Flanagan, Dennis C.; Moriasi, Daniel N.; Fortuna, Ann-Marie; Starks, Patrick
Abstract: A new modeling platform was developed to simulate spatially distributed sediment production and transport in agricultural landscapes. The sediment production at the grid scale was computed using the stand-alone Water Erosion Prediction Project-Hillslope Erosion code, while an advection-dispersion equation represented sediment transport. The model's performance was tested in the Water Resources and Erosion watersheds at the Oklahoma and Central Plains Agricultural Research Center, El Reno, OK, USA. Results showed that this modeling approach could capture the complex behavior of sediment under different management practices in the watersheds. The modeling framework provides mechanistic processes to simulate the fate and transport of sediment across the watershed at spatio-temporal scales that are useful in assessing the environmental impacts of management schemes. Therefore, this study is expected to help advance the current approaches to estimating soil erosion by bridging scale differences to capture the large-scale effects of small-scale soil erosion processes. Highlights: A new modeling framework was developed for estimating soil erosion. Sediment production is evaluated in fully distributed settings. Different sizes of sediment are considered in simulations. The model provides mechanistic processes in simulating sediment transport. The model is able to capture changes in land and management practices.